Enhancing Creative Thinking Skills in High School Students through the Integrated Approach of Joyful Learning and Problem-Based Learning - Algiranto; Anderias Henukh; Tutik Yuliatun; Parlindungan Sinaga; Jesi Jecsen Pongkendek; Izak Habel Wayangkau; Mohd Zaidi Bin Amiruddin (Universitas Syiah Kuala, 2026)
The integrated approach of Joyful Learning and Problem-Based Learning (PBL) is a learning strategy that synergizes an enjoyable, pressure-free learning atmosphere with structured, real-world problem-solving challenges1. This study aims to examine the effectiveness of this approach in enhancing the creative thinking skills of high school students in Physics in Papua. This study employed a quasi-experimental method involving 80 students equally divided into an experimental class and a control class. An open-ended essay test instrument was utilized to measure indicators of fluency, flexibility, originality, and elaboration. The analysis results indicated that while initial abilities were equivalent (p > 0.05), there was a highly significant difference in post-test results (p < 0.001) following the intervention6. The experimental class recorded a mean score of 81.88, outperforming the control class which obtained 66.25, with an effect size (Cohen's d) of 1.498. These findings demonstrate that the blend of emotional comfort and cognitive stimulation is effective in significantly enhancing student creative thinking skills.